EDUCATION OF BANJAR FISHERMEN'S CHILDREN IN KARANG ANYAR VILLAGE SECANGGANG SUBDISTRICT LANGKAT REGENCY - Shella Lorenza; Syarbaini Saleh; Yummy Jumiati Marsa (UNIVERSITAS PAKUAN, 2022)
This study aims to describe qualitatively the portrait of children's education from the perspective of the Banjar tribal fishing community in Karang Anyar Village, this phenomenon is very interesting and important to study scientifically. The methods used in this research are observation, interview, and documentation methods. The data analysis techniques used are data reduction, data display, and data verification. This is dominated by parents who have misconceptions (misunderstanding) about education who think that there is no point in sending their children to school because it only adds to the economic burden and they are simply given education at home so that it is better for these children to help their parents earn a living at home. sea because of going to school, in the end, to get a degree and earn an income. This is what makes the level of education of children in this region is very minimal. The factors causing the lack of children's education in this village are the lack of parental participation in education, economic conditions and environmental influences that are too urgent and the children's income too early, the crisis of solidarity, the relatively high pessimistic attitude of the community, the lack of cooperation between teachers, parents, community leaders, and religious leaders.